Responsibility Accounting in the Era of Artificial Intelligence and Big Data - Alimuddin Alimuddin; Asri Usman; Andreas Caesario Mangeka; Muh. Faiz Qaidhan Jamsir; Muhajir Muhajir (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the transformation of Responsibility Accounting (RA) in the era of Artificial Intelligence (AI) and Big Data Analytics (BDA). Using a literature review approach, the research explores how digital technologies enhance the function of RA as a management control tool and evidence-based decision-making system. The findings indicate that the integration of AI and BDA improves the efficiency, accuracy, and relevance of accounting information through automated reporting, anomaly detection, and predictive analysis. Furthermore, technologies such as machine learning, natural language processing, and blockchain strengthen organizational transparency and accountability. However, several challenges remain, including legacy system integration, data security and privacy issues, and regulatory uncertainty regarding AI. The success of digital RA implementation depends on organizational readiness in data governance, technological infrastructure, and human resource competency. Consequently, the future of RA is expected to evolve toward a more predictive, interactive, and transparent system driven by big data and intelligent algorithms.